KONSTRUKSI REALITAS PADA KASUS KEKERASAN SEKSUAL OLEH GURU BESAR FARMASI UNIVERSITAS GADJAH MADA (ANALISIS FRAMING KUMPARAN.COM) - Suciningsih, Mutia; Silvina Mayasari; Sari Ekowati (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Sexual violence is one of the most common types of human rights violations in Indonesia. It is not "new" that sexual violence cases are currently a hot topic of conversation until now. As in the case of sexual violence committed by a Professor of Pharmacy at Gadjah Mada University (UGM) as reported by online media Kumparan.com. The purpose of this study is to find out how Robert N. Entman's framing model in the construction of sexual violence carried out by a professor at the Faculty of Pharmacy, Gadjah Mada University (UGM) on Kumparan.com online media. This study uses a descriptive qualitative approach with the Robert N. Entman’s model framing analysis method. The research was conducted by analyzing the content of news using four framing elements, including, Define Problems, Diagnose Causes, Make Moral Judgment and Treatment Recommendation. The results of the study show the construction of reality in the media Kumparan.com argue that the case is a serious issue that must be handled transparently and firmly from the institution and the government. The framing obtained in this study is: Frame on Punishment Enforcement and Discipline, Frame on Victim Protection and Social Impact, Frame on Academic Morality and Ethics and Frame on Administrative and Personnel Processes.